Pembangunan aplikasi penjualan dan stok barang Pada toko nuansa elektronik pacitan - Nurcahyono, Fendi (APMMI - Asosiasi Profesi Multimedia Indonesia, 2012)
ABSTRACT: At Shades of Electronics Stores Pacitan, recording and data processing of goods, quantity and price of goods, data suppliers, and sales transaction data is still done using hand-written. Difficulties in recording and counting the number of types of goods, quantity of goods, as well as the large number of prices, resulting in the data obtained to be less accurate. To improve the accuracy of the data, required the construction of the sale of information systems are computerized. Application of sale of goods is made by using the manufacturer's software as the main interface of PHP and MySQL as its database. This program allows the user to input data, edit data, delete data, search data, filtering data and media data to the printing paper. Data is entered in the form of data items, data suppliers, data types and data items the sale of goods. While the resulting output is a report system information data items, reporting of data suppliers, data sales of goods and a memorandum of sale of goods. Keywords: Applications Sales and Stock Goods Â ABSTRAKSI : Pada Toko Nuansa Elektronik Pacitan, pencatatan dan pengolahan data barang, jumlah dan harga barang, data para supplier, serta data transaksi penjualan masih dilakukan dengan menggunakan tulisan tangan. Kesulitan dalam mencatat dan menghitung banyaknya jenis barang, jumlah barang, maupun besarnya jumlah harga, mengakibatkan data yang diperoleh menjadi kurang akurat. Untuk meningkatkan keakuratan data, diperlukan pembangunan sistem informasi penjualan barang yang terkomputerisasi. Aplikasi penjualan barang ini dibuat dengan menggunakan software PHP sebagai pembuat interface utama dan MySQL sebagai basis datanya. Program ini memungkinkan user untuk input data, edit data, hapus data, pencarian data, penyaringan data dan pencetakan data ke media kertas. Data yang diinputkan berupa data barang, data supplier, data jenis barang dan data penjualan barang. Sedangkan output yang dihasilkan sistem informasi ini berupa laporan data barang, laporan data supplier, data penjualan barang dan nota transaksi penjualan barang. Kata Kunci : Aplikasi Penjualan dan Stok Barang